The effect of fertilizer systems on the main nutrition elements content in soil and winter wheat yield components - Korotkova, I.; Karasenko, V. (Scientific Progress & Innovations, 2023)
The obtaining grain of high and stable quality largely depends on a scientifically based method of the fertilizers applying in combination with growth stimulators and microelements that activate the life plants processes, increase yield and quality of products, strengthen the protective potential and improve tolerance to adverse cultivation con-ditions. The study aim is to determine the effectiveness of the mineral fertilizers with humic preparation mixtures on the dynamics of the main nutrients content (nitrogen, phosphorus and potassium) in the soil and on the winter wheat yield components. The experimental study was carried on typical heavy loam chernozems in the Poltava regions using soft winter wheat Podolyanka cultivar. The experimental design provided for six fertilization systems: ammonium nitrate, urea, carbamide-ammonia mixture (CAM) and their mixtures with Humisol-prima. The experi-mental design provided for six fertilization systems: ammonium nitrate, urea, carbamide-ammonia mixture and their mixtures with Humisol-prima. The significant effect of the nitrogen fertilizers mixtures with humic preparation: urea + Humisol-prima and CAM + Humisol-prima on the nutrients' accumulation in the soil were determined. The use of the urea + Humisol-prima mixture contributed to an increase in the alkaline hydrolysable nitrogen content by 6.1 %, total nitrogen content by 14 %, mobile phosphorus – by 18.8 %, and exchangeable potassium – by 23 % compared to pure urea. The maximum increase in the main nutrients content in the soil was observed when applying of CAM + Humisol-prima (1:1) mixture compared to the use of pure CAM: alkaline hydrolysable nitrogen – by 8 %, total nitrogen – by 17 %, mobile phosphorus – by 24.1 % and exchangeable potassium – by 23 %. The use of mixtures of nitrogen fertilizers with a humic preparation ensured an intensive increase in the main indicators of the yield structure elements. It was found that obtaining maximum values of the yield structure elements is possible under using of CAM + Humisol-prima mixture (relative to pure CAM): an increase in productive tillering by 17.1 %, grain weight per spike – by 22.4 %, 1000-grain weight – by 11 %.